Human herpesvirus-8: beyond Kaposi's - Rimar, Doron; Rimar, Yossi; Keynan, Yoav (The Israel Medical Association journal, 2006)
Today, more than 10 years and 2000 articles since human herpesvirus 8 was first described by Chang et al., novel insights into the transmission and molecular biology of HHV-8 have unveiled a new spectrum of diseases attributed to the virus. The association of HHV-8 with proliferative disorders--including Kaposi's sarcoma, multicentric Castleman disease and primary effusion lymphoma--is well established. Other aspects of HHV-8 infection are currently the subject of accelerated research. Primary HHV-8 infection may manifest as a mononucleosis-like syndrome in the immunocompetent host, or in various forms in the immunocompromised host. The association of HHV-8 with primary pulmonary hypertension was observed by Cool et al. in 2003, but six clinical trials evaluating the role of HHV-8 in pulmonary hypertension have not been able to replicate this intriguing observation. It has been speculated that HHV-8 may secondarily infect proliferating endothelium in patients with pulmonary hypertension. HHV-8 epidemiology, modes of transmission, new spectrum of disease and treatment are presented and discussed.